2015
DOI: 10.1093/rheumatology/kev112
|View full text |Cite
|
Sign up to set email alerts
|

International Consensus for ultrasound lesions in gout: results of Delphi process and web-reliability exercise

Abstract: This, the first consensus-based US definition of elementary lesions in gout, demonstrated good reliability overall. It constitutes an essential step in developing a core outcome measurement that permits a higher degree of homogeneity and comparability between multicentre studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
104
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 141 publications
(111 citation statements)
references
References 30 publications
1
104
0
2
Order By: Relevance
“…The unweighted κ values for all 4 lesions when reading the static images ranged from moderate to almost perfect for interobserver reliability (0.54-0.98), and similar results were found for the intrareader reliability (0.65-0.93). The US lesion with a higher level of reliability among the participants was the DC (intrareader: 0.98 and inter-reader: 0.93) whereas the lowest level of agreement was seen for the soft tissue aggregates (intrareader: 0.54 and inter-reader: 0.65) 14 .…”
Section: Current Limitations Of Us In Gout Assessmentmentioning
confidence: 92%
See 2 more Smart Citations
“…The unweighted κ values for all 4 lesions when reading the static images ranged from moderate to almost perfect for interobserver reliability (0.54-0.98), and similar results were found for the intrareader reliability (0.65-0.93). The US lesion with a higher level of reliability among the participants was the DC (intrareader: 0.98 and inter-reader: 0.93) whereas the lowest level of agreement was seen for the soft tissue aggregates (intrareader: 0.54 and inter-reader: 0.65) 14 .…”
Section: Current Limitations Of Us In Gout Assessmentmentioning
confidence: 92%
“…The first step was to obtain consensus-based definitions for the US elementary lesion as indicated by the literature review. This was accomplished by performing a Delphi exercise 14 . Thirty-five rheumatologists performing US and with an interest in gout were invited to participate, and 32 responded positively.…”
Section: Current Limitations Of Us In Gout Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound of the knees and the first toes showed typical features of gout, ie, tophi, aggregates, double contour sign, and erosions ( Fig. 2) [2,3]. Double contour was detected in both first MTP joints and at the inter-condylar femoral region of both knees.…”
Section: Case Reportmentioning
confidence: 93%
“…By using a previous systematic literature review, 4 elementary US components were identified, i.e., double contour sign, aggregates, tophi, and erosion 17 . The US definitions of these 4 identified lesions were agreed upon by the group using a Delphi exercise 18 . Subsequently, the metric properties of these components were …”
Section: Journal Of Rheumatologymentioning
confidence: 99%